Análisis de la causa No. 02331-2016-01633 dentro del juicio ejecutivo en relación con el derecho al debido proceso, la seguridad jurídica y la tutela judicial efectiva. - Poma Carvajal, Jessica Marielena (2020)
Man, by nature and since time immemorial, has fought as an independent being, but at the same time he needs to coexist with more people, that is why over time the idea of a society evolved and took on different nuances, even what we see today. Together with the advent of society, it became necessary to create Law, that is, clear rnles that regulate it, to live in peace and harmony. Within the law we have two doctrines that have transcended within the law; the first is Ius naturalism, which are the inherent, immutable principles of the person, that which emanates from the very nature of man; and secondly, the Ius Positivism, which are the norms, laws that follow a certain process of creation to reach a promulgation and subsequent obedience, which is why the object as such of the law is to regulate the conduct of human beings through of legal nmms. The rights (inherent to the human being) and its regulations (mies of common obedience) are derived from the aforementioned. The Constitution of the Republic in Ecuador and in all countries, is the highest standard within the nations and from this the rights and guarantees that citizens possess are derived. Our Magna Carta recognizes a right that has been quite popular within Ius naturalism and that at present was embodied within positive law; This right is "the right to resistance", also used by citizens as a right of direct patiicipation within power. This right, more than being recognized, has not been adequately developed for the proper exercise by citizens, since there is no suitable procedure for invocation and its mechanism for enforceability is almost nil.